Deformability of Short Steel Reinforced Concrete Structures on Light Concrete - Semko, Oleksandr; Dariienko, Viktor; Sirobaba, Vitaliy (International Journal of Engineering and Technology, 2018)
The calculation, modeling and experimental research of steel-concrete tubular elements made of thin-walled galvanized sheet metal and lightweight concrete have been carried out. The proposed type of structures can be used as a separate structure in the form of a column or a pillar, and one of the types of the reinforcement of a certain light structure. The basic technological and constructive requirements for manufacturing and further exploitation of structures are given. For determination of actual workâ€™s indexes of constructions experimental research of standards are undertaken, and recommendations on adjustment of well-known calculation formulas of close constructions as for structural parameters are given. The design (modeling) was performed in MSC / Nastran software. An analysis of the proposed structures use is carried out with the corresponding conclusions.Â